2019
DOI: 10.5194/acp-19-9399-2019
|View full text |Cite
|
Sign up to set email alerts
|

Predicted ultrafine particulate matter source contribution across the continental United States during summertime air pollution events

Abstract: Abstract. The regional concentrations of airborne ultrafine particulate matter mass (Dp<0.1 µm; PM0.1) were predicted in 39 cities across the United States (US) during summertime air pollution episodes. Calculations were performed using a regional source-oriented chemical transport model with 4 km spatial resolution operating on the National Emissions Inventory created by the U.S. Environmental Protection Agency (EPA). Measured source profiles for particle size and composition between 0.01 and 10 µm were us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…This has increased the Cr/PM 2.5 ratio by more than a factor of three from 2001 to 2016 (figures S2-S21). Differences in the PM 2.5 trends compared to those of the individual metals are consistent with predictions of ultrafine particle concentrations (PM 0.1 ) in urban areas across the US [55]. Similar to PM metals, ultrafine particles are dominated by primary emissions in urban areas, especially during pollution episodes, whereas major contributors PM 2.5 (e.g.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This has increased the Cr/PM 2.5 ratio by more than a factor of three from 2001 to 2016 (figures S2-S21). Differences in the PM 2.5 trends compared to those of the individual metals are consistent with predictions of ultrafine particle concentrations (PM 0.1 ) in urban areas across the US [55]. Similar to PM metals, ultrafine particles are dominated by primary emissions in urban areas, especially during pollution episodes, whereas major contributors PM 2.5 (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to PM metals, ultrafine particles are dominated by primary emissions in urban areas, especially during pollution episodes, whereas major contributors PM 2.5 (e.g. organics, sulfate, nitrate, ammonium) are predominantly secondary in origin [55]. A separate study similarly concluded that metals exhibit much greater spatial variability than PM 2.5 mass across the US due to the high contribution and regional nature of secondary PM formation [56].…”
Section: Discussionmentioning
confidence: 97%
“…The current study focuses on outdoor exposure to UFPs that may be useful in future epidemiological studies. Indoor or in-vehicle exposure to UFPs can also be significant (Wallace and Ott, 2011;Rim et al, 2010;Bhangar et al, 2011;Weichenthal et al, 2015;Fruin et al, 2008) but characterizing these micro-environments is beyond the scope of the current paper.…”
Section: Discussionmentioning
confidence: 99%
“…Nonresidential natural gas combustion was deemed the chief source of UFPs across the major cities therein. On-road gasoline and diesel vehicles contributed, on average, 14% to regional UFP emissions, which could have been underestimated due to measurement limitations 42 .…”
Section: Major Sources Of Anthropogenic Outdoor Ufpsmentioning
confidence: 99%